Penerapan Program Pengembangan Karyawan Dalam Menghadapi Era Industri 4.0 - Nurnaningsih, Nurnaningsih (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to evaluate the employee development strategy implemented by PT Telkom Indonesia in facing the challenges of Industry 4.0, focusing on the effectiveness of digital training, employee participation, perceptions, competency improvement, and implementation obstacles. Using a descriptive quantitative and qualitative approach through interviews, observation, and documentation with 15 informants, the findings indicate that Telkom has adopted relevant digital training programs such as AI, cloud computing, and data analytics via the MyDigilearn platform. Employee participation is high, with 83% of respondents feeling more prepared to face new technologies. However, challenges remain, including overly theoretical training methods, inflexible schedules, and suboptimal post-training evaluations. Only 46% received adequate coaching experiences, and 39% noted insufficient training evaluations. Despite these issues, Telkom’s training strategy aligns with human capital development principles and the 70:20:10 learning model. Improvements are recommended in delivery methods, schedule flexibility, and continuous evaluation to enhance program effectiveness.